2008
DOI: 10.1902/jop.2008.080139
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes in Healthy and Diseased Gingival Tissues

Abstract: Gingival tissue transcriptomes provide a valuable scientific tool for further hypothesis-driven studies of the pathobiology of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
178
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(186 citation statements)
references
References 34 publications
8
178
0
Order By: Relevance
“…First, we evaluated the expression of NK cell-related genes in human periodontitis lesions (n ϭ 241, from 120 patients each contributing Ն2 diseased tissue samples, with a mean probing pocket depth [PPD] of 6.58 Ϯ 1.91 mm; range, 4 to 11 mm) compared to clinically healthy gingivae (n ϭ 69, each patient contributing a healthy tissue sample, when available; PPD, 2.29 Ϯ 0.52 mm; range, 1 to 4 mm) (18,19). As summarized in Table 1, the predominant NK cell-activating gene with increased expression in periodontitis lesions versus health was the CRACC gene (3.18-fold; false discovery rate [FDR] ϭ 5.24 ϫ 10 Ϫ30 ); high correlation of array data and quantitiative PCR (qPCR) findings for this gene (Spearman's r ϭ Ϫ0.81; P ϭ 0.005) was shown previously (26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we evaluated the expression of NK cell-related genes in human periodontitis lesions (n ϭ 241, from 120 patients each contributing Ն2 diseased tissue samples, with a mean probing pocket depth [PPD] of 6.58 Ϯ 1.91 mm; range, 4 to 11 mm) compared to clinically healthy gingivae (n ϭ 69, each patient contributing a healthy tissue sample, when available; PPD, 2.29 Ϯ 0.52 mm; range, 1 to 4 mm) (18,19). As summarized in Table 1, the predominant NK cell-activating gene with increased expression in periodontitis lesions versus health was the CRACC gene (3.18-fold; false discovery rate [FDR] ϭ 5.24 ϫ 10 Ϫ30 ); high correlation of array data and quantitiative PCR (qPCR) findings for this gene (Spearman's r ϭ Ϫ0.81; P ϭ 0.005) was shown previously (26).…”
Section: Resultsmentioning
confidence: 99%
“…Whole-genome gene expression profiles were generated using Affymetrix HG-U133plus 2.0 gene arrays from 310 gingival tissue samples (69 clinically healthy and 241 diseased) from 120 nonsmoking patients (55 with aggressive and 65 with chronic periodontitis) phenotyped with respect to demographic information, clinical periodontal status, and levels of subgingival bacteria with respect to 11 species, as described previously (18,19) (Columbia University Medical Center IRB approval number AAAB0896; GEO [Gene Expression Omnibus at the NCBI] accession number GSE16134). Data were analyzed using R/Bioconductor (limma and SPIA packages) and SAS (for population-specific expression analysis [PSEA] [20]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have earlier presented gingival tissue transcriptomic data from the same patients (Demmer et al, 2008;Papapanou et al, 2009), and demonstrated substantial differential gene expression between states of periodontal health and disease. Here, we extend this work and analyze differential expression of miRNAs in the same samples.…”
Section: Discussionmentioning
confidence: 99%
“…We used 310 Affymetrix HG-U133Plus2.0 microarray samples (GEO accession number GSE16134) of 'healthy' [n = 69, no bleeding on probing (BoP), probing depth (PD) ≤ 4 mm, and clinical attachment loss (CAL) ≤ 4 mm)] or 'diseased' gingival tissue samples (n = 241; with BoP, PD ≥ 4 mm, and CAL ≥ 3 mm), obtained from 120 non-smoking, systemically healthy individuals with moderate/severe periodontitis (65 with CP and 55 with AgP), as previously described (Demmer et al, 2008;Kebschull and Papapanou, 2010). Excellent correlation of array data and confirmatory qPCR was shown previously (Papapanou et al, 2009).…”
Section: Methodsmentioning
confidence: 99%